Cassava Bagasse as a Low-Cost Substrate for Cellulase and Organic Acid Production Using Co-Cultivated Fungi - Analdi Farniga; Phimrak Khaokhajorn; Songsak Wattanachaisaereekul (Fermentation, 2023)
Cassava bagasse has great potency as a substrate in the biorefinery industry. This paper proposes the valorisation of cassava bagasse into organic acids by cellulase through the co-cultivation of Aspergillus violaceofuscus and Trichoderma reesei RUT-C30 at the ratio 1:1. The optimised conditions for β-glucosidase production under submerged fermentation were pH 4.50, a tween 80 concentration of 0.05% (v/v), and a spore concentration of 7.18 × 107 spores·mL−1. We found base steam cassava bagasse (BSCB) to have high cellulose content, making it possible to replace avicel phosphoric acid swollen cellulose (PASC) as a substrate. The co-cultivation with the BSCB substrate had higher levels of β-glucosidase (1.72-fold), cellobiohydrolase (2.83-fold), and endoglucanase (2.82-fold) activity compared to that of the avicel PASC substrate. Moreover, acetic acid (7.41 g·L−1), citric acid (3.54 g·L−1), gluconic acid (0.30 g·L−1), and malic acid (0.37 g·L−1) were detected in the BSCB crude extract. These results demonstrate the considerable prospects of the A. violaceofuscus and T. reesei RUT-C30 co-cultivation approaches in the biorefinery industry.
Keywords: Biofuel production and bioconversion; Enzyme Production and Characterization; Enzyme Catalysis and Immobilization